2018
DOI: 10.3390/atmos9070267
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of PM2.5 during Haze and Non-Haze Episodes in Wuxi, China

Abstract: Chemical characteristics of fine particulate matter (PM 2.5 ) in Wuxi at urban, industrial, and clean sites on haze and non-haze days were investigated over four seasons in 2016. In this study, high concentrations of fine particulate matter (107.6 ± 25.3 µg/m 3 ) were measured in haze episodes. The most abundant chemical components were organic matter (OM), SO 4 2− , NO 3 − , elemental carbon (EC), and NH 4 + , which varied significantly on haze and non-haze days. The concentrations of OM and EC were 38.5 ± 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The following references appear in the supplemental information: Chen et al., 2018b ; Deng et al., 2011; Gao et al., 2018 ; Huang et al., 2010 ; Li et al., 2015 ; State Council of the People's Republic of China, 2013 ; Wang et al., 2016 .…”
Section: Supporting Citationsmentioning
confidence: 99%
“…The following references appear in the supplemental information: Chen et al., 2018b ; Deng et al., 2011; Gao et al., 2018 ; Huang et al., 2010 ; Li et al., 2015 ; State Council of the People's Republic of China, 2013 ; Wang et al., 2016 .…”
Section: Supporting Citationsmentioning
confidence: 99%
“…𝐸𝐹, 𝐹𝑄, 𝐸 𝑝𝑝 _𝑐𝑓 , and 𝐸 𝑝𝑝 are obtained from the literatureTong et al, 2018;Yun et al, 2020;MEE, 2020;Wang et al, 2020;Tang et al, 2020;Lin et al, 2021;Chen et al, 2022). More and more studies(Hodan et al, 2004;Chen et al, 2018; Zhang 225 et al, 2022) showed that in China, the proportion of secondary and primary PM2.5 mass to the total PM2.5 mass is close, so we assume that they account for 50% respectively. Figure2showed the emission reduction design for perturbed emissions.https://doi.org/10.5194/egusphere-2023-2615 Preprint.…”
mentioning
confidence: 99%